miR-132/212 Impairs Cardiomyocytes Contractility in the Failing Heart by Suppressing SERCA2a - Lei, Zhiyong; Wahlquist, Christine; el Azzouzi, Hamid; Deddens, Janine C.; Kuster, Diederik; van Mil, Alain; Rojas-Munoz, Agustin; Huibers, Manon M.; Mercola, Mark; de Weger, Roel; Van der Velden, Jolanda; Xiao, Junjie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Compromised cardiac function is a hallmark for heart failure, mostly appearing as decreased con-tractile capacity due to dysregulated calcium handling. Unfortunately, the underlying mechanism causing impaired calcium handling is still not fully understood. Previously the miR-132/212 family was identified as a regulator of cardiac function in the failing mouse heart, and pharmaceutically inhibition of miR-132 is beneficial for heart failure. In this study, we further investigated the mo-lecular mechanisms of miR-132/212 in modulating cardiomyocyte contractility in the context of the pathological progression of heart failure. We found that upregulated miR-132/212 expressions in all examined hypertrophic heart failure mice models. The overexpression of miR-132/212 prolongs calcium decay in isolated neonatal rat cardiomyocytes, whereas cardiomyocytes isolated from miR-132/212 KO mice display enhanced contractility in comparison to wild type controls. In response to chronic pressure-overload, miR-132/212 KO mice exhibited a blunted deterioration of cardiac function. Using a combination of biochemical approaches and in vitro assays, we confirmed that miR-132/212 regulates SERCA2a by targeting the 3’-end untranslated region of SERCA2a. Additionally, we also identified PTEN as a direct target of miR-132/212 and potentially participates in the cardiac response to miR132/212. In end-stage heart failure patients, miR-132/212 is upregulated and correlates with reduced SERCA2a expression. The up-regulation of miR-132/212 in heart failure impairs cardiac contractile function by targeting SERCA2a, suggesting that pharmaceutical inhibition of miR-132/212 might be a promising thera-peutic approach to promote cardiac function in heart failure patients.